Morphometric Analysis of Hippocampal Pyramidal Neurons in situ and in Grafts Developing in the Anterior Eye Chambers of Young and Aged Wistar Rats. (1997) - Zhuravleva, Z. N.; Saifullina, V. N.; Zenchenko, C. I.
Abstract : We performed a morphometric analysis of the somatic and nuclear areas in the pyramidal neurons of the hippocampal fields CA1 and CA3 in situ and in grafts developing for six weeks in the anterior eye chambers of young (3-to-9 wk.) and of aged (18-to-19.5 mos.) Wistar rats. The mean areas of the CA1 pyramidal somata and nuclei were significantly decreased in the aged animals in situ . The mean parameters of the CA3 pyramidal neurons were not changed, although their distribution was different (bimodal versus unimodal in the young animals). In both groups of recipients, the areas of CA1 neurons and of their nuclei were significantly larger in the grafted tissue than those found in situ . The areas of CA3 neurons did not show any difference in aged recipients and demonstrated only slight hypertrophy in young recipients. We concluded that the area sizes of the pyramidal cell bodies and nuclei in CA1 neurons are more sensitive than those of CA3 neurons to both aging and transplantation. The age of recipients did not significantly influence the growth and development of grafted pyramidal cells.